Binder aqueous solution for lithium ion battery, slurry for negative electrode of lithium ion battery, negative electrode for lithium ion battery, and lithium ion battery

By using a water-soluble poly(meth)acrylamide aqueous binder solution, the problem of reducing softness of the adhesive for lithium-ion batteries during cross-linking is solved, and good adhesion and efficient discharge of the electrode are achieved. Capacity maintenance rate.

CN112531163BActive Publication Date: 2025-02-18ARAKAWA CHEM IND LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202010966619.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-17
Filing Date
2020-09-15
Publication Date
2025-02-18
Estimated Expiration
2040-09-15

AI Technical Summary

Technical Problem

The existing adhesive for lithium-ion batteries leads to a decrease in flexibility during the cross-linking process, which in turn affects the adhesion and circulation characteristics of the electrode.

Method used

An aqueous binder solution containing water-soluble poly(meth)acrylamide is used, the water-soluble polymer consisting of a predetermined unsaturated monomer and contains 30 mol% to 95 mol% of a (meth)acrylamide group-containing compound. and 5 mol % to 40 mol % of alkoxyalkyl (meth)acrylate.

Benefits of technology

The storage stability of the slurry for the negative electrode of lithium-ion batteries is improved, the flexibility and adhesion of the electrode are enhanced, and the discharge capacity maintenance rate is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002682557000000041
    Figure BDA0002682557000000041
  • Figure BDA0002682557000000071
    Figure BDA0002682557000000071
  • Figure BDA0002682557000000081
    Figure BDA0002682557000000081
Patent Text Reader

Abstract

[Technical Problem] Provide an aqueous binder solution for lithium-ion battery electrodes, a slurry for lithium-ion battery negative electrodes, a negative electrode for lithium-ion batteries, and a lithium-ion battery. [Technical Means] The present disclosure provides an aqueous binder solution for lithium-ion batteries, which contains a water-soluble poly(meth)acrylamide (A), wherein the water-soluble poly(meth)acrylamide (A) is a polymer of a monomer group, and relative to 100 mol % of the monomer group, the monomer group contains 30 mol % to 95 mol % of a (meth)acrylamide-containing compound (a) and 5 mol % to 40 mol % of an alkoxyalkyl (meth)acrylate (b) represented by the following general formula (1), CH2=C(R 1 )‑CO‑O‑R 2 ‑O‑R 3 (1) In the formula, R 1 is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 4 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms; in addition, R 1 , R 2 and R 3 The total number of carbon atoms in the group is 5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a binder aqueous solution for lithium ion batteries, a slurry for a negative electrode of lithium ion batteries, a negative electrode for lithium ion batteries, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and have been used in a wide range of applications. Therefore, in recent years, research has been conducted on improving battery components such as electrodes in order to further improve the performance of lithium-ion batteries.

[0003] The positive and negative electrodes of lithium-ion batteries are manufactured by the following method: a slurry formed by dispersing an electrode active material and a binder resin in a solvent is applied to both sides of a current collector (such as a metal foil), the solvent is dried and removed to form an electrode layer, and then the electrode layer is compression-molded using a roller press or the like.

[0004] In recent years, various electrode active materials have been proposed in lithium ion battery electrodes from the viewpoint of increasing battery capacity. However, depending on the electrode active material, expansion and contraction are easily generated with charge and discharge. Therefore, the lithium ion battery electrode that is easily expanded and contracted with charge and discharge undergoes volume changes (resilience) compared to the initial stage due to repeated charge and discharge, and the electrical characteristics such as the cycle characteristics of the lithium ion battery using the lithium ion battery electrode are easily reduced.

[0005] Therefore, in this field, attempts are being made to use binder resins to solve the above technical problems. For example, it is proposed to obtain good charge and discharge characteristics by using polyacrylamide as a binder of a water-soluble resin (Patent Documents 1 and 2). In addition, for the expansion and contraction accompanying the charge and discharge of the active material, it is proposed to suppress the expansion by adding a crosslinking agent to the particulate resin as a binder resin (Patent Document 3). The crosslinking agent usually undergoes a crosslinking reaction in the drying step after applying the slurry composition to the collector, and forms crosslinks between particles of the particulate resin.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-118908

[0009] Patent Document 2: Japanese Patent Application Publication No. 2015-106488

[0010] Patent Document 3: International Publication No. 2015 / 098507 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] However, when cross-linking is performed using a cross-linking agent, the flexibility of the binder resin decreases, and as a result, there is a problem that the adhesion to the electrode decreases.

[0013] Therefore, the technical problem to be solved by the present invention is to provide a good lithium ion battery binder aqueous solution that provides a good discharge capacity retention rate for lithium ion batteries, good electrode flexibility and electrode adhesion for electrodes, and good storage stability for slurry.

[0014] Technical means to solve technical problems

[0015] The present inventors have conducted intensive studies and have found that the above-mentioned technical problems can be solved by using a water-soluble polymer having a predetermined unsaturated monomer as a constituent component.

[0016] The following items are provided according to the present disclosure.

[0017] (Item 1)

[0018] A binder aqueous solution for lithium ion batteries, comprising a water-soluble poly(meth)acrylamide (A),

[0019] The water-soluble poly(meth)acrylamide (A) is a polymer of a monomer group, wherein the monomer group comprises 30 mol% to 95 mol% of a (meth)acrylamide group-containing compound (a) and 5 mol% to 40 mol% of an alkoxyalkyl (meth)acrylate (b) represented by the following general formula (1), relative to 100 mol% of the monomer group.

[0020] CH2=C(R 1 )-CO-OR 2 -OR 3 (1)

[0021] In the formula, R 1 is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 4 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms; in addition, R 1 , R 2 and R 3 The total number of carbon atoms in the group is 5 or less.

[0022] (Item 2)

[0023] A slurry for a negative electrode of a lithium ion battery comprising the aqueous binder solution for a lithium ion battery as described in the above item and a negative electrode active material.

[0024] (Item 3)

[0025] A negative electrode for a lithium ion battery is obtained by applying the slurry for a negative electrode for a lithium ion battery as described in the above item on a current collector and drying and solidifying it.

[0026] (Item 4)

[0027] A lithium ion battery comprising the negative electrode for a lithium ion battery as described in the above item.

[0028] In the present disclosure, in addition to the combinations explicitly described, one or more of the above features may be provided in further combinations.

[0029] Beneficial Effects

[0030] The binder aqueous solution for lithium ion batteries of the present invention can give excellent storage stability to the slurry for negative electrodes of lithium ion batteries. In addition, the slurry for negative electrodes of lithium ion batteries of the present invention has excellent storage stability. In addition, the electrode of the present invention has excellent flexibility and adhesion. Moreover, the battery of the present invention has excellent discharge capacity retention rate. DETAILED DESCRIPTION

[0031] In the entire scope of the present disclosure, the range of the numerical values ​​of each physical property value, content, etc. can be appropriately set (for example, selected from the upper and lower limit values ​​described in each of the following items). Specifically, with respect to the numerical value α, when A4, A3, A2, A1 (A4>A3>A2>A1) and the like are exemplified as the upper and lower limits of the numerical value α, the range of the numerical value α is exemplified as less than A4, less than A3, less than A2, more than A1, more than A2, more than A3, A1-A2, A1-A3, A1-A4, A2-A3, A2-A4, A3-A4, etc.

[0032] [Aqueous binder solution for lithium-ion battery electrodes: also called aqueous solution]

[0033] The present disclosure provides a binder aqueous solution for lithium ion batteries, wherein the binder aqueous solution for lithium ion batteries comprises a water-soluble poly(meth)acrylamide (A),

[0034] The water-soluble poly(meth)acrylamide (A) is a polymer of a monomer group, wherein the monomer group comprises 30 mol% to 95 mol% of a (meth)acrylamide group-containing compound (a) and 5 mol% to 40 mol% of an alkoxyalkyl (meth)acrylate (b) represented by the following general formula (1), relative to 100 mol% of the monomer group.

[0035] CH2=C(R 1 )-CO-OR 2 -OR 3 (1)

[0036] In the formula, R 1is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 4 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms; in addition, R 1 , R 2 and R 3 The total number of carbon atoms in the group is 5 or less.

[0037] <Water-soluble poly(meth)acrylamide: also referred to as component (A)>

[0038] In the present disclosure, "water-soluble" means that when 0.5 g of the compound is dissolved in 100 g of water at 25°C, the insoluble component is less than 0.5% by mass (less than 2.5 mg).

[0039] When the component (A) is not water-soluble, it does not form an aqueous solution because it is insoluble in water. As a result, the component (A) does not contribute to the dispersion of the slurry. In addition, the slurry cannot be given the viscosity required for coating on the collector.

[0040] When 0.5 g of the component (A) is dissolved in 100 g of water, the insoluble content of the component (A) is, for example, less than 0.5 mass %, less than 0.4 mass %, less than 0.3 mass %, less than 0.2 mass %, less than 0.1 mass %, or 0 mass %.

[0041] In the present disclosure, “poly(meth)acrylamide” refers to a (co)polymer obtained by polymerizing a monomer group including a (meth)acrylamide group-containing compound ((co)polymer).

[0042] In the present disclosure, “(meth)acrylic acid” means “at least one selected from the group consisting of acrylic acid and methacrylic acid”. Similarly, “(meth)acrylate” means “at least one selected from the group consisting of acrylate and methacrylate”. Furthermore, “(meth)acryloyl” means “at least one selected from the group consisting of acryloyl and methacryloyl”.

[0043] <(Meth)acrylamide-containing compound (a): also referred to as component (a)>

[0044] In the present disclosure, "a (meth)acrylamide group-containing compound" refers to a compound having a (meth)acrylamide group. The (meth)acrylamide group-containing compound can be any known compound without particular limitation, and can be used alone or in combination of two or more.

[0045] In one embodiment, the (meth)acrylamide-containing compound is represented by the following structural formula:

[0046] [Chemistry 1]

[0047]

[0048] (Where R 1 is a hydrogen atom or a methyl group; R 2 and R 3 are each independently a hydrogen atom, a substituted or unsubstituted alkyl group, or an acetyl group, or R 2 and R 3 are groups that together form a ring structure; R 4 and R 5 are each independently a hydrogen atom, a substituted or unsubstituted alkyl group, a hydroxyl group, an amino group (-NR a R b (R a and R b Each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group) or an acetyl group. Examples of substituents of the substituted alkyl group include hydroxyl, amino, acetyl, and the like. 2 and R 3 Examples of the groups that form a ring structure together include morpholino and the like. )

[0049] Examples of the alkyl group include a linear alkyl group, a branched alkyl group, and a cycloalkyl group.

[0050] Straight chain alkyl is composed of the general formula -C n H 2n+1 (n is an integer greater than or equal to 1). Examples of the linear alkyl group include methyl, ethyl, propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl.

[0051] The branched alkyl group is a group in which at least one hydrogen atom of a linear alkyl group is substituted by an alkyl group. Examples of the branched alkyl group include isopropyl, isobutyl, sec-butyl, tert-butyl, diethylpentyl, trimethylbutyl, trimethylpentyl, and trimethylhexyl.

[0052] Examples of the cycloalkyl group include a monocyclic cycloalkyl group, a bridged ring cycloalkyl group, and a condensed ring cycloalkyl group.

[0053] In the present disclosure, a monocyclic ring refers to a ring structure formed by a covalent bond of carbon and having no internal bridge structure. In addition, a fused ring refers to a ring structure in which two or more monocyclic rings share two atoms (i.e., each ring only shares (condenses) one side with each other). A bridged ring refers to a ring structure in which two or more monocyclic rings share three or more atoms.

[0054] Examples of the monocyclic cycloalkyl group include cyclopentyl, cyclohexyl, cycloheptyl, cyclodecyl, and 3,5,5-trimethylcyclohexyl.

[0055] Examples of the bridged cycloalkyl group include tricyclodecanyl, adamantyl, and norbornyl.

[0056] Examples of the fused ring cycloalkyl group include bicyclodecanyl and the like.

[0057] Examples of the (meth)acrylamide group-containing compound (a) include (meth)acrylamide, N-isopropyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, diacetone (meth)acrylamide, maleic acid amide, (meth)acrylamide tert-butyl sulfonic acid, (meth)acryloyl morpholine, hydroxyethyl (meth)acrylamide, and salts thereof; examples of the salt include dimethylaminopropyl (meth)acrylamide methyl chloride quaternary salt (Methyl quaternary salt), dimethylaminoethyl (meth)acrylate benzyl chloride quaternary salt (benzyl chloride quaternary salt), and the like. Among them, when (meth)acrylamide, particularly acrylamide, is used, a binder having high water solubility, high interaction with the electrode active material, high dispersibility in the slurry and high adhesion between the electrode active materials in the electrode can be produced.

[0058] The upper and lower limits of the content of the (meth)acrylamide group-containing compound relative to 100 mol% of the monomer group are exemplified by 95 mol%, 90 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 65 mol%, 60 mol%, 55 mol%, 50 mol%, 45 mol%, 40 mol%, 35 mol%, 30 mol%, etc. In one embodiment, the range of the above content is preferably 30 mol% to 95 mol%.

[0059] The upper and lower limits of the content of the (meth)acrylamide group-containing compound relative to 100 mass% of the monomer group are exemplified by 95 mass%, 90 mass%, 85 mass%, 80 mass%, 75 mass%, 70 mass%, 65 mass%, 60 mass%, 55 mass%, 50 mass%, 45 mass%, 40 mass%, 35 mass%, 30 mass%, 25 mass%, 20 mass%, etc. In one embodiment, the content of the (meth)acrylamide group-containing compound relative to 100 mass% of the monomer group is preferably 20 mass% to 95 mass%.

[0060] <(Meth)acrylate alkoxyalkyl ester (b): also referred to as component (b)>

[0061] Component (b) is a compound represented by the following general formula (1):

[0062] CH2=C(R 1 )-CO-OR 2 -OR 3 (1)

[0063] (Where R1 is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 4 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms; in addition, R 1 , R 2 and R 3 The total number of carbon atoms of the group is 5 or less).

[0064] As the alkoxyalkyl (meth)acrylate, various known alkoxyalkyl (meth)acrylates can be used without particular limitation, and they can be used alone or in combination of two or more.

[0065] R 1 , R 2 and R 3 The upper and lower limits of the total number of carbon atoms of the group are exemplified by 5, 4, 3, 2, etc. In one embodiment, from the viewpoint of ensuring the water solubility of the component (A) and the ease of obtaining, R 1 , R 2 and R 3 The total number of carbon atoms of the group is specified to be 5 or less. This is because when the total number of carbon atoms exceeds 5, the water solubility of the (meth)acrylate alkoxyalkyl ester decreases, and it is difficult to ensure the water solubility of the (A) component. In addition, from the perspective of further improving the storage stability of the negative electrode slurry, the softness and adhesion of the negative electrode, and the discharge capacity retention rate of the lithium ion battery, the above carbon number is preferably 4 or less. In addition, from the same perspective, R 3 The number of carbon atoms is preferably 1.

[0066] In the general formula (1), by making R 1 , R 2 and R 3 The total number of carbon atoms of the group is 5 or less, and the reasons for improving the storage stability of the negative electrode slurry, the softness and adhesion of the negative electrode, and the discharge capacity retention rate of the lithium ion battery are as follows. In addition, the following is only a theory and is not intended to limit the present invention to this.

[0067] In the general formula (1), R 1 , R 2 and R 3 A monomer having a total carbon number of more than 5 in the group is a hydrophobic monomer. When such a hydrophobic monomer is used to manufacture component (A), the water solubility of component (A) decreases. Therefore, the surface tension of the aqueous solution containing component (A) decreases. As a result, when the aqueous solution containing component (A) is used to manufacture the slurry, it becomes easy to generate bubbles. If bubbles are generated, the following problems will occur.

[0068] (1) When producing the slurry, the blades of the disperser collide with the bubbles, and the slurry is not dispersed, resulting in poor storage stability.

[0069] (2) When a slurry containing bubbles is applied to a current collector to produce an electrode, the dried and solidified electrode will have holes caused by the bubbles. Cracks and peeling will occur starting from these holes, resulting in reduced flexibility and adhesion of the electrode.

[0070] Based on the above, it is considered that if the water solubility of component (A) is improved, that is, if R 1 , R 2 and R 3 When the total number of carbon atoms of the groups is 5 or less, the storage stability of the negative electrode slurry, the flexibility and adhesion of the negative electrode, and the discharge capacity retention rate of the lithium ion battery are improved.

[0071] R 1 , R 2 and R 3 The combination of groups shown below is exemplified as an example.

[0072] [Table 1]

[0073]

[0074]

[0075] Me:Methyl (-CH3)

[0076] R 2 The left side is the ester bond side, and the right side is the alkoxy group side.

[0077] Examples of the alkoxyalkyl (meth)acrylate include methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 1-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-methoxypropyl (meth)acrylate, 1-methoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-methoxybutyl (meth)acrylate, 1-methoxybutyl (meth)acrylate, ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 1-ethoxyethyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 2-ethoxypropyl (meth)acrylate, 1-ethoxypropyl (meth)acrylate, propoxymethyl (meth)acrylate, 2-propoxyethyl (meth)acrylate, 1-propoxyethyl (meth)acrylate, butoxymethyl (meth)acrylate, and the like.

[0078] The upper and lower limits of the content of the alkoxyalkyl (meth)acrylate relative to 100 mol% of the monomer group are exemplified by 40 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 9 mol%, 5 mol%, etc. In one embodiment, the content is preferably in the range of 5 mol% to 40 mol%.

[0079] The upper and lower limits of the content of the alkoxyalkyl (meth)acrylate relative to 100 mass% of the monomer group are exemplified by 60 mass%, 55 mass%, 50 mass%, 45 mass%, 40 mass%, 35 mass%, 30 mass%, 25 mass%, 20 mass%, 15 mass%, 10 mass%, 5 mass%, etc. In one embodiment, the content of the alkoxyalkyl (meth)acrylate is preferably 5 mass% to 60 mass% relative to 100 mass% of the monomer group.

[0080] <Unsaturated organic acid or salt thereof (c): also referred to as component (c)>

[0081] In the present disclosure, an unsaturated organic acid refers to a compound having an acidic group and a polymerizable unsaturated bond. The unsaturated organic acid may be used alone or in combination of two or more.

[0082] The salt of an unsaturated organic acid refers to the salt of the above-mentioned unsaturated organic acid. The salt of an unsaturated organic acid may be used alone or in combination of two or more.

[0083] Examples of the unsaturated organic acid include unsaturated carboxylic acid, unsaturated sulfonic acid, and unsaturated phosphoric acid.

[0084] Examples of the unsaturated carboxylic acid include (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid.

[0085] Examples of the unsaturated sulfonic acid include α,β-ethylenically unsaturated sulfonic acids such as vinylsulfonic acid, styrylsulfonic acid, and (meth)allylsulfonic acid; (meth)acrylamide-tert-butylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-(meth)acrylamide-2-hydroxypropanesulfonic acid, 3-sulfopropane (meth)acrylate, and bis-(3-sulfopropyl)itaconate.

[0086] Examples of the unsaturated phosphoric acid include vinylphosphonic acid, vinyl phosphate, bis((meth)acryloyloxyethyl)phosphate, diphenyl-2-(meth)acryloyloxyethyl phosphate, dibutyl-2-(meth)acryloyloxyethyl phosphate, dioctyl-2-(meth)acryloyloxyethyl phosphate, monomethyl-2-(meth)acryloyloxyethyl phosphate, and 3-(meth)acryloyloxy-2-hydroxypropanephosphoric acid.

[0087] In the present disclosure, a compound that belongs to both the (meth)acrylamide group-containing compound and the unsaturated organic acid is an unsaturated organic acid.

[0088] Examples of the salt of an unsaturated organic acid include inorganic salts of unsaturated organic acids. The inorganic salt of an unsaturated organic acid refers to a salt whose cation part is a metal cation. Examples of the inorganic salt include alkali metal salts, alkaline earth metal salts, and the like.

[0089] Examples of the alkali metal include lithium, sodium, and potassium.

[0090] Examples of the alkaline earth metal include magnesium and calcium.

[0091] The upper and lower limits of the content of the unsaturated organic acid or its salt relative to 100 mol% of the monomer group are exemplified as 40 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 5 mol%, 0 mol%, etc. In one embodiment, the above content is preferably 0 mol% to 40 mol%; from the viewpoint of improving the water solubility and slurry dispersibility of the (A) component, the above content is more preferably 10 mol% to 40 mol%.

[0092] The upper and lower limits of the content of the unsaturated organic acid or its salt relative to 100 mass % of the monomer group are exemplified by 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 5 mass %, 0 mass %, etc. In one embodiment, the content of the unsaturated organic acid or its salt is preferably 0 mass % to 50 mass % relative to 100 mass % of the monomer group.

[0093] <Hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms (d): also referred to as component (d)>

[0094] As the component (d), various known components can be used without particular limitation, and the component (d) may be used alone or in combination of two or more.

[0095] In the present disclosure, a "hydroxyalkyl group having 2 to 4 carbon atoms" refers to a group in which one of the hydrogen atoms constituting an alkyl group having 2 to 4 carbon atoms is substituted with a hydroxy group.

[0096] Examples of the hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms include 1-hydroxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxy-1-methylethyl (meth)acrylate, 1-hydroxy-2-methylethyl (meth)acrylate, 1-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate. 4-Hydroxybutyl acrylate, 1-hydroxy-1-methyl-propyl (meth)acrylate, 2-hydroxy-1-methyl-propyl (meth)acrylate, 3-hydroxy-1-methyl-propyl (meth)acrylate, 1-ethyl-2-hydroxyethyl (meth)acrylate, 1-hydroxy-2-methyl-propyl (meth)acrylate, 2-hydroxy-2-methyl-propyl (meth)acrylate, 3-hydroxy-2-methyl-propyl (meth)acrylate, 1,1-dimethyl-2-hydroxyethyl (meth)acrylate, and the like.

[0097] The upper and lower limits of the content of the hydroxyalkyl (meth)acrylate having a hydroxyalkyl group with 2 to 4 carbon atoms relative to 100 mol% of the monomer group are exemplified as 40 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 5 mol%, 0 mol%, etc. In one embodiment, the above content is preferably 0 mol% to 40 mol%; from the viewpoint of improving the water solubility of the (A) component and the flexibility of the electrode, the above content is more preferably 5 mol% to 40 mol%.

[0098] The upper and lower limits of the content of the hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms relative to 100 mass% of the monomer group are exemplified by 40 mass%, 35 mass%, 30 mass%, 25 mass%, 20 mass%, 15 mass%, 10 mass%, 5 mass%, 0 mass%, etc. In one embodiment, the content of the hydroxyalkyl (meth)acrylate (d) having a hydroxyalkyl group having 2 to 4 carbon atoms is preferably 0 mass% to 40 mass% relative to 100 mass% of the monomer group.

[0099] <α,β-Unsaturated Nitrile (e): Also referred to as Component (e)>

[0100] α,β-unsaturated nitriles can be used alone or in combination of two or more. α,β-unsaturated nitriles can be suitably used for the purpose of imparting flexibility to electrodes. Examples of α,β-unsaturated nitriles include (meth)acrylonitrile, α-chloro(meth)acrylonitrile, α-ethyl(meth)acrylonitrile, vinylidene cyanide, etc. Among them, (meth)acrylonitrile is preferred, and acrylonitrile is particularly preferred.

[0101] The upper and lower limits of the content of α,β-unsaturated nitrile relative to 100 mol% of the monomer group are exemplified as 40 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 5 mol%, 0 mol%, etc. In one embodiment, the above content is preferably 0 mol% to 40 mol%; from the viewpoint of improving the flexibility of the electrode, the above content is more preferably 5 mol% to 40 mol%.

[0102] The upper and lower limits of the content of the α,β-unsaturated nitrile relative to 100 mass % of the monomer group are exemplified by 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 5 mass %, 0 mass %, etc. In one embodiment, the content of the α,β-unsaturated nitrile (e) is preferably 0 mass % to 30 mass % relative to 100 mass % of the monomer group.

[0103] <Relative Ratio of Monomer Components>

[0104] The upper and lower limits of the molar ratio of the component (b) to the component (a) contained in the monomer group [the amount of the substance of the component (b) / the amount of the substance of the component (a)] are exemplified by 1.3, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, etc. In one embodiment, the molar ratio is preferably 0.05 to 1.3.

[0105] The upper and lower limits of the molar ratio of any one of the components (c) to (e) to the component (a) contained in the monomer group [the amount of any one of the components (c) to (e) / the amount of the component (a)] are exemplified by 1.3, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0, etc. In one embodiment, the molar ratio is preferably 0 to 1.3.

[0106] The upper and lower limits of the molar ratio of any one of the components (c) to (e) to the component (b) contained in the monomer group [the amount of any one of the components (c) to (e) / the amount of the component (b)] are exemplified by 8, 7, 6, 5, 4, 3, 2, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0, etc. In one embodiment, the molar ratio is preferably 0 to 8.

[0107] The upper and lower limits of the mass ratio of the component (b) to the component (a) contained in the monomer group [mass of the component (b) / mass of the component (a)] are exemplified by 3, 2.5, 2, 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, etc. In one embodiment, the mass ratio is preferably 0.05 to 3.

[0108] The upper and lower limits of the mass ratio of the component (c) to the component (a) contained in the monomer group [mass of the component (c) / mass of the component (a)] are exemplified by 2.5, 2, 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0, etc. In one embodiment, the mass ratio is preferably 0 to 2.5.

[0109] The upper and lower limits of the mass ratio of the component (d) to the component (a) contained in the monomer group [mass of the component (d) / mass of the component (a)] are exemplified by 2, 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0, etc. In one embodiment, the mass ratio is preferably 0 to 2.

[0110] The upper and lower limits of the mass ratio of the component (e) to the component (a) contained in the monomer group [mass of the component (e) / mass of the component (a)] are exemplified by 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0, etc. In one embodiment, the mass ratio is preferably 0 to 1.5.

[0111] The upper and lower limits of the mass ratio of the component (c) to the component (b) contained in the monomer group [mass of the component (c) / mass of the component (b)] are exemplified by 10, 9, 8, 7, 6, 5, 4, 3, 2, 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0, etc. In one embodiment, the mass ratio is preferably 0 to 10.

[0112] The upper and lower limits of the mass ratio of the component (d) to the component (b) contained in the monomer group [mass of the component (d) / mass of the component (b)] are exemplified by 8, 7, 6, 5, 4, 3, 2, 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0, etc. In one embodiment, the mass ratio is preferably 0 to 8.

[0113] The upper and lower limits of the mass ratio of the component (e) to the component (b) contained in the monomer group [mass of the component (e) / mass of the component (b)] are exemplified by 6, 5, 4, 3, 2, 1.5, 1, 0.9, 0.5, 0.2, 0.1, 0.09, 0.05, 0, etc. In one embodiment, the mass ratio is preferably 0 to 6.

[0114] <Monomers that are not any of the components (a) to (e): also referred to as other components>

[0115] In the above monomer group, monomers other than any of components (a) to (e) (other components) may be used unless the desired effects of the present invention are impaired. As other components, various well-known components may be used alone or in combination of two or more.

[0116] Examples of other components include unsaturated carboxylic acid esters not containing a hydroxyl group, conjugated dienes, and aromatic vinyl compounds.

[0117] The hydroxyl-free unsaturated carboxylic acid ester is preferably a hydroxyl-free (meth)acrylate. Examples of the hydroxyl-free (meth)acrylate include a hydroxyl-free linear (meth)acrylate, a hydroxyl-free branched (meth)acrylate, a hydroxyl-free alicyclic (meth)acrylate, and a hydroxyl-free substituted (meth)acrylate.

[0118] Examples of the hydroxyl-free linear (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and decyl (meth)acrylate.

[0119] Examples of the branched (meth)acrylate not containing a hydroxyl group include isopropyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.

[0120] Examples of the alicyclic (meth)acrylate not containing a hydroxyl group include cyclohexyl (meth)acrylate and the like.

[0121] Examples of the substituted (meth)acrylate not containing a hydroxyl group include glycidyl (meth)acrylate, allyl (meth)acrylate, and ethylene di(meth)acrylate.

[0122] The substituted (meth)acrylate not containing a hydroxyl group also includes alkoxyalkyl (meth)acrylates other than the alkoxyalkyl (meth)acrylate represented by the general formula (1).

[0123] The unsaturated carboxylic acid ester containing no hydroxyl group can be suitably used for the purpose of imparting flexibility to the electrode. From the above viewpoint, the content of the unsaturated carboxylic acid ester containing no hydroxyl group is preferably less than 40 mol% (e.g., less than 30 mol%, less than 20 mol%, less than 19 mol%, less than 15 mol%, less than 10 mol%, less than 5 mol%, less than 1 mol%, 0 mol%) relative to 100 mol% of the above monomer group.

[0124] In addition, relative to 100 mass % of the above-mentioned monomer group, the content of the unsaturated carboxylic acid ester not containing a hydroxyl group is preferably 40 mass % or less (for example, less than 30 mass %, less than 20 mass %, less than 19 mass %, less than 15 mass %, less than 10 mass %, less than 5 mass %, less than 1 mass %, 0 mass %).

[0125] Examples of the conjugated diene include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted straight-chain conjugated pentadiene, and substituted side-chain conjugated hexadiene (substituted and side-chain conjugated hexadiene).

[0126] From the viewpoint of the cycle characteristics of the lithium ion battery, the content of the conjugated diene is preferably less than 10 mol %, more preferably 0 mol %, based on 100 mol % of the monomer group.

[0127] The upper and lower limits of the content of the conjugated diene relative to 100 mass % of the monomer group are exemplified by 30 mass %, 20 mass %, 10 mass %, 5 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 30 mass %.

[0128] Examples of the aromatic vinyl compound include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, and divinylbenzene.

[0129] From the viewpoint of the cycle characteristics of the lithium ion battery, the content of the aromatic vinyl compound is preferably less than 10 mol %, more preferably 0 mol %, based on 100 mol % of the monomer group.

[0130] The upper and lower limits of the content of the aromatic vinyl compound relative to 100 mass % of the monomer group are exemplified by 30 mass %, 20 mass %, 10 mass %, 5 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 30 mass %.

[0131] As for the ratio of the above-mentioned unsaturated carboxylic acid ester not containing hydroxyl group, the above-mentioned conjugated diene, and other components other than the above-mentioned aromatic vinyl compound in the above-mentioned monomer group, examples thereof include less than 10 mol%, less than 5 mol%, less than 2 mol%, less than 1 mol%, less than 0.1 mol%, less than 0.01 mol%, and 0 mol%, relative to 100 mol% of the above-mentioned monomer group. In addition, examples thereof include less than 10 mass%, less than 9 mass%, less than 7 mass%, less than 5 mass%, less than 4 mass%, less than 2 mass%, less than 1 mass%, less than 0.9 mass%, less than 0.5 mass%, less than 0.3 mass%, less than 0.1 mass%, less than 0.05 mass%, less than 0.01 mass%, and 0 mass%, relative to 100 mass% of the above-mentioned monomer group.

[0132] <Method for producing component (A)>

[0133] The component (A) can be synthesized using various known polymerization methods, preferably using a free radical polymerization method. Specifically, it is preferred to add a free radical polymerization initiator and, if necessary, a chain transfer agent to a monomer mixture containing the above components, and perform a polymerization reaction at a reaction temperature of 50° C. to 100° C. while stirring. The reaction time is not particularly limited, but is preferably 1 to 10 hours.

[0134] The free radical polymerization initiator is not particularly limited, and various known free radical polymerization initiators can be used. Examples of free radical polymerization initiators include persulfates such as potassium persulfate and ammonium persulfate; redox polymerization initiators in which the above persulfates are combined with reducing agents such as sodium bisulfite; azo initiators such as 2,2′-azobis-2-amidinopropane dihydrochloride, etc. The amount of the free radical polymerization initiator used is not particularly limited, and is preferably 0.05% to 5.0% by mass, and more preferably 0.1% to 3.0% by mass, relative to 100% by mass of the monomer group providing component (A).

[0135] Before the free radical polymerization reaction and / or when the obtained component (A) is dissolved in water, the pH of the reaction solution may be adjusted using a common neutralizing agent such as ammonia and organic amines, potassium hydroxide, sodium hydroxide, lithium hydroxide, etc., for the purpose of improving the manufacturing stability. In this case, the pH is preferably 2 to 11. In addition, ethylenediaminetetraacetic acid (EDTA) or its salts may be used as metal ion sealants for the same purpose.

[0136] When component (A) has an acid group (acid group), it can be used by adjusting the appropriate neutralization rate according to the application (a neutralization rate of 100% means neutralization with a base of the same molar number as the acid component contained in component (A); a neutralization rate of 50% means neutralization with a base of half the molar number of the acid component contained in component (A)). The neutralization rate when dispersing the electrode active material is not particularly limited. In one embodiment, it is preferably 95% to 100% after the formation of a coating, etc. From the viewpoint of preventing the initial capacity from decreasing, it is preferably 95% or more; from the viewpoint of preventing hydrolysis, it is preferably less than 100%. Examples of neutralizing salts include Li salts, Na salts, K salts, ammonium salts, Mg salts, Ca salts, Zn salts, Al salts, and the like.

[0137] In one embodiment, the component (A) is preferably an inorganic salt. The inorganic salt of the component (A) refers to a salt whose cation part is a metal cation. Examples of the inorganic salt include the above-mentioned inorganic salts.

[0138] <(A) Physical properties of components>

[0139] The upper limit and lower limit of the glass transition temperature of the component (A) are exemplified by 160°C, 155°C, 150°C, 145°C, 140°C, 135°C, 130°C, 125°C, 120°C, 115°C, 110°C, 105°C, 100°C, 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C, 60°C, 55°C, 50°C, 45°C, 40°C, 35°C, 30°C, 25°C, 20°C, 15°C, 10°C, 5°C, 0°C, etc. In one embodiment, it is preferably 0°C or higher, and more preferably 30°C or higher from the viewpoint of mechanical strength and heat resistance.

[0140] The glass transition temperature of the component (A) can be adjusted by the combination of monomers. The glass transition temperature of the component (A) can be determined from the glass transition temperature (Tg, absolute temperature: K) of the homopolymer of the monomers and their mass fractions according to the Fox equation shown below.

[0141] 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+(W3 / Tg3)+…+(W n / Tg n )

[0142] [Wherein, Tg represents the glass transition temperature (K) of the polymer to be determined, W1~W n Indicates the mass fraction of each monomer, Tg1~Tg n represents the glass transition temperature (K) of each monomer homopolymer].

[0143] For example, the glass transition temperature is 165°C for acrylamide homopolymers, 106°C for acrylic acid homopolymers, -15°C for hydroxyethyl acrylate homopolymers, and 105°C for acrylonitrile homopolymers. In order to obtain the (A) component having the desired glass transition temperature, the composition of the monomers constituting it can be determined. In addition, the glass transition temperature of the homopolymer of the monomer can be measured by DSC (differential scanning calorimeter), DTA (differential thermal analyzer), TMA (thermomechanical measuring device), etc., for example, under conditions of heating from -100°C to 300°C (heating rate 10°C / min.). In addition, the values ​​recorded in the literature can also be used. The literature exemplifies "Chemical Handbook (Chemical Handbook) Basics II Edited by the Chemical Society of Japan (Revised 5th Edition)", p325, etc.

[0144] The weight average molecular weight (Mw) of the component (A) is not particularly limited, and the upper and lower limits thereof are exemplified by 7 million, 6.5 million, 6 million, 5.5 million, 5 million, 4.5 million, 4 million, 3.5 million, 3 million, 2.5 million, 2 million, 1.5 million, 1 million, 950,000, 900,000, 850,000, 800,000, 750,000, 700,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 350,000, 300,000, 250,000, 200,000, 150,000, 100,000, etc. In one embodiment, from the viewpoint of dispersion stability of the slurry, it is preferably 100,000 to 7 million, and more preferably 350,000 to 6 million.

[0145] The number average molecular weight (Mn) of the component (A) is not particularly limited, and the upper and lower limits thereof are exemplified by 6,000,000, 5,500,000, 5,000,000, 4,500,000, 4,000,000, 3,500,000, 3,000,000, 2,500,000, 2,000,000, 1,500,000, 950,000, 900,000, 850,000, 800,000, 750,000, 700,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 300,000, 200,000, 100,000, 50,000, 10,000, etc. In one embodiment, the number average molecular weight (Mn) of the component (A) is preferably 10,000 or more.

[0146] The weight average molecular weight and the number average molecular weight can be determined as polyacrylic acid-equivalent values ​​measured by gel permeation chromatography (GPC) in an appropriate solvent, for example.

[0147] The upper and lower limits of the molecular weight distribution (Mw / Mn) of the component (A) are exemplified by 15, 14, 13, 11, 10, 9, 7.5, 5, 4, 3, 2.9, 2.5, 2, 1.5, 1.1, etc. In one embodiment, the molecular weight distribution (Mw / Mn) of the component (A) is preferably 1.1-15.

[0148] The B-type viscosity of the aqueous solution containing 13% by mass of the component (A) is not particularly limited, and the upper and lower limits thereof are exemplified by 100,000 mPa·s, 90,000 mPa·s, 80,000 mPa·s, 70,000 mPa·s, 60,000 mPa·s, 50,000 mPa·s, 45,000 mPa·s, 40,000 mPa·s, 30,000 mPa·s, 20,000 mPa·s, 10,000 mPa·s, 9000 mPa·s, 8000 mPa·s, 7000 mPa·s, 6000 mPa·s, 5000 mPa·s, 4000 mPa·s, 3000 mPa·s, 2000 mPa·s, 1000 mPa·s, 900 mPa·s, 700 mPa·s, 500 mPa·s, 300 mPa·s, 200 mPa·s, and 100 mPa·s. In one embodiment, the B-type viscosity is preferably in the range of 100 mPa·s to 100,000 mPa·s.

[0149] The B-type viscosity is measured using a B-type viscometer such as "B-type Viscometer BM" manufactured by Toki Sangyo Co., Ltd.

[0150] The upper and lower limits of the pH of the aqueous solution of the binder for lithium ion batteries are exemplified by 9, 8.9, 8.5, 8, 7.9, 7.5, 7, 6.9, 6.5, 6, 5.9, 5.6, 5.5, 5.4, 5.2, 5.1, 5, 4, etc. In one embodiment, from the viewpoint of solution stability, the pH of the aqueous solution of the binder for lithium ion batteries is preferably pH 4 to 9, more preferably pH 4 to 7.

[0151] The pH can be measured at 25° C. using a glass electrode pH meter (for example, manufactured by Horiba, Ltd., product name “pH meter D-52”).

[0152] The upper and lower limits of the content of the component (A) relative to 100% by mass of the aqueous binder solution for lithium ion batteries are exemplified by 20% by mass, 19% by mass, 15% by mass, 14% by mass, 12% by mass, 10% by mass, 9% by mass, 7% by mass, 6% by mass, 5% by mass, etc. In one embodiment, the content of the component (A) relative to 100% by mass of the aqueous binder solution for lithium ion batteries is preferably 5% to 20% by mass.

[0153] The upper and lower limits of the water content relative to 100 mass % of the lithium ion battery binder aqueous solution are exemplified by 95 mass %, 90 mass %, 85 mass %, 80 mass %, etc. In one embodiment, the water content relative to 100 mass % of the lithium ion battery binder aqueous solution is preferably 80 mass % to 95 mass %.

[0154] The upper and lower limits of the mass ratio of the component (A) contained in the aqueous lithium ion battery binder solution to water are 0.25, 0.2, 0.15, 0.1, 0.05, etc. In one embodiment, the mass ratio of the component (A) contained in the aqueous lithium ion battery binder solution to water is preferably 0.05 to 0.25.

[0155] <Dispersion (emulsion)>

[0156] In one embodiment, the aqueous binder solution for lithium ion batteries contains a dispersion (emulsion).

[0157] Examples of the dispersion (emulsion) include styrene-butadiene copolymer latex, polystyrene polymer latex, polybutadiene polymer latex, acrylonitrile-butadiene copolymer latex, polyurethane polymer latex, polymethyl methacrylate polymer latex, methyl methacrylate-butadiene copolymer latex, polyacrylate polymer latex, vinyl chloride polymer latex, vinyl acetate polymer emulsion, vinyl acetate-ethylene copolymer emulsion, polyethylene emulsion, carboxyl-modified styrene-butadiene copolymer resin emulsion, acrylic resin emulsion, polyethylene, polypropylene, polyethylene terephthalate, polyamide (PA), polyimide (PI), polyamideimide (PAI), aromatic polyamide, alginic acid and its salts, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), etc.

[0158] Relative to 100 mass % of (A) component, the upper and lower limits of the content of the dispersion (emulsion) are exemplified by 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 19 mass %, 17 mass %, 15 mass %, 13 mass %, 10 mass %, 9 mass %, 7 mass %, 5 mass %, 4 mass %, 2 mass %, 1 mass %, 0 mass %, etc. In one embodiment, from the viewpoint of anti-resistance to rebound and discharge capacity retention rate, the addition amount of the dispersion (emulsion) is preferably 0 mass % to 50 mass % relative to 100 mass % of (A) component.

[0159] <Additives>

[0160] The aqueous binder solution for lithium ion batteries may contain a substance that is not included in any of the (A) component, water, and dispersion (emulsion) as an additive.

[0161] Examples of the additives include a dispersant, a leveling agent, an antioxidant, and a thickener.

[0162] The content of the additive relative to 100 mass % of the component (A) is exemplified by 0 mass % to 5 mass %, less than 1 mass %, less than 0.1 mass %, less than 0.01 mass %, 0 mass %, etc. In one embodiment, from the viewpoint of generating HAZE in the adhesive when the content exceeds 5 mass %, the content of the additive relative to 100 mass % of the component (A) is preferably 5 mass % or less.

[0163] Furthermore, examples include 0% to 5% by mass, less than 1% by mass, less than 0.1% by mass, less than 0.01% by mass, and 0% by mass, relative to 100% by mass of the aqueous solution.

[0164] Examples of the dispersant include anionic dispersants, cationic dispersants, nonionic dispersants, and polymer dispersants.

[0165] Examples of the leveling agent include surfactants such as alkyl surfactants, silicon surfactants, fluorine surfactants, and metal surfactants. By using a surfactant, craters generated during coating can be prevented and the smoothness of the slurry layer (coating) can be improved.

[0166] Examples of the antioxidant include phenol compounds, hydroquinone compounds, organic phosphine compounds, sulfur compounds, phenylenediamine compounds, polymer phenol compounds, etc. The polymer phenol compound is a polymer having a phenol structure in the molecule. The weight average molecular weight of the polymer phenol compound is preferably 200 to 1000, more preferably 600 to 700.

[0167] Examples of thickeners include cellulose polymers such as carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, and their ammonium salts and alkali metal salts; (modified) poly(meth)acrylic acid and their ammonium salts and alkali metal salts; (modified) polyvinyl alcohol, copolymers of acrylic acid or acrylic acid salts and vinyl alcohol, polyvinyl alcohols such as copolymers of maleic anhydride or maleic acid or fumaric acid and vinyl alcohol; polyethylene glycol, polyethylene oxide, polyvinyl pyrrolidone, modified polyacrylic acid, oxidized starch, starch phosphate, casein, various modified starches, acrylonitrile-butadiene copolymer hydrogenates, etc.

[0168] The lithium ion battery binder aqueous solution can be used as a lithium ion battery electrode binder aqueous solution or a lithium ion battery negative electrode binder aqueous solution.

[0169] [Lithium-ion battery negative electrode slurry: also called slurry]

[0170] The present disclosure provides a slurry for a negative electrode of a lithium ion battery, comprising the above-mentioned aqueous binder solution for lithium ion battery electrodes and a negative electrode active material (B).

[0171] In this disclosure, "slurry" refers to a suspension of liquid and solid particles.

[0172] The upper and lower limits of the content of the component (A) relative to 100% by mass of the slurry are exemplified by 99.9% by mass, 95% by mass, 90% by mass, 80% by mass, 70% by mass, 60% by mass, 50% by mass, 40% by mass, 30% by mass, 20% by mass, 10% by mass, 5% by mass, 1% by mass, 0.5% by mass, 0.2% by mass, 0.1% by mass, etc. In one embodiment, the component (A) is contained in an amount of 0.1% to 99.9% by mass relative to 100% by mass of the slurry.

[0173] Examples of water include ultrapure water, pure water, distilled water, ion-exchanged water, and tap water.

[0174] The upper and lower limits of the water content relative to 100 mass % of the slurry are exemplified by 70 mass %, 65 mass %, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, etc. In one embodiment, the water content is preferably 30 mass % to 70 mass % relative to 100 mass % of the slurry.

[0175] <Negative Electrode Active Material (B): Also Called (B) Component>

[0176] The negative electrode active material may be used alone or in combination of two or more.

[0177] As long as it is a material that can reversibly absorb and release lithium, the negative electrode active material is not particularly limited, and a suitable material can be appropriately selected according to the type of the target lithium ion battery, and can be used alone or in combination of two or more. Examples of the negative electrode active material include carbon materials and silicon materials, oxides containing lithium atoms, lead compounds, tin compounds, arsenic compounds, antimony compounds, and aluminum compounds that are alloyed with lithium.

[0178] Examples of the above-mentioned carbon materials include graphite (also called black lead, examples include natural graphite, artificial graphite, etc.) as highly crystalline carbon, low-crystalline carbon (soft carbon, hard carbon), carbon black (ketjen black, acetylene black, channel black, lamp black, oil furnace black, thermal black, etc.), fullerenes, carbon nanotubes, carbon nanofibers, carbon nanohorns, carbon fibrils, mesophase carbon microbeads (MCMB), pitch-based carbon fibers, etc.

[0179] The silicon material includes SiC, SiO x C y (0<x≤3, 0<y≤5); Si3N4; Si2N2O; with SiO x Silicon oxide composites represented by (0<x≤2) (for example, materials described in Japanese Patent Publication No. 2004-185810 and Japanese Patent Publication No. 2005-259697); silicon materials described in Japanese Patent Publication No. 2004-185810, etc. In addition, silicon materials described in Japanese Patent No. 5390336 and Japanese Patent No. 5903761 can also be used.

[0180] The silicon oxide is preferably of the composition formula SiO x Silicon oxide represented by (0<x<2, preferably 0.1≤x≤1).

[0181] The silicon alloy is preferably an alloy of silicon and at least one transition metal, and the transition metal is selected from the group consisting of titanium, zirconium, nickel, copper, iron and molybdenum. These transition metal silicon alloys have high electronic conductivity and high strength, so they are preferred. The silicon alloy is more preferably a silicon-nickel alloy or a silicon-titanium alloy, and is particularly preferably a silicon-titanium alloy. Relative to 100 mol% of the metal element in the silicon alloy, the content of silicon in the silicon alloy is preferably 10 mol% or more, and more preferably 20 mol% to 70 mol%. In addition, the silicon material can be any of single crystal, polycrystalline and amorphous.

[0182] In addition, when a silicon material is used as the negative electrode active material, a negative electrode active material other than a silicon material may be used in combination. Examples of such negative electrode active materials include the above-mentioned carbon material; conductive polymers such as polyphenylene; X B Y O Z (A represents an alkali metal or a transition metal; B represents at least one transition metal selected from cobalt, nickel, aluminum, tin, manganese, etc.; O represents an oxygen atom; X, Y and Z are numbers in the range of 0.05<X<1.10, 0.85<Y<4.00, 1.5<Z<5.00, respectively) represented by a composite metal oxide; and other metal oxides, etc. When a silicon material is used as a negative electrode active material, the volume change accompanying the absorption and release of lithium is small, so it is preferably used in combination with a carbon material.

[0183] Examples of the above-mentioned oxides containing lithium atoms include ternary nickel cobalt manganese oxide, lithium-manganese composite oxides (LiMn2O4, etc.), lithium-nickel composite oxides (LiNiO2, etc.), lithium-cobalt composite oxides (LiCoO2, etc.), lithium-iron composite oxides (LiFeO2, etc.), lithium-nickel-manganese composite oxides (LiNi 0.5 Mn 0.5 O2, etc.), lithium-nickel-cobalt composite oxide (LiNi 0.8 Co 0.2 O2, etc.), lithium-transition metal phosphate compounds (LiFePO4, etc.) and lithium-transition metal sulfate compounds (Li x Fe2(SO4)3), lithium-titanium composite oxide (lithium titanate: Li4Ti5O 12 ) and other lithium-transition metal composite oxides and other previously known negative electrode active materials.

[0184] From the viewpoint of significantly exerting the effects of the present invention, the carbon material and / or the material alloying with lithium contained in the negative electrode active material is preferably 50 mass % or more, more preferably 80 mass % or more, further preferably 90 mass % or more, particularly preferably 100 mass %.

[0185] In one embodiment, the negative electrode active material (B) is preferably a negative electrode active material containing more than 1 mass % (more than 2 mass %, more than 5 mass %, more than 10 mass %, more than 25 mass %, more than 50 mass %, more than 75 mass %, more than 90 mass %, 100 mass %) of silicon and / or silicon oxide covered with a carbon layer.

[0186] The shape of the negative electrode active material is not particularly limited, and can be any shape such as microparticles and thin films, preferably microparticles. The average particle size of the negative electrode active material is not particularly limited, and its upper and lower limits are exemplified by 50μm, 45μm, 40μm, 35μm, 30μm, 25μm, 20μm, 15μm, 10μm, 5μm, 4μm, 3μm, 2.9μm, 2μm, 1μm, 0.5μm, 0.1μm, etc. More specifically, in one embodiment, from the viewpoint of uniformly forming a thin coating film, if it is above 0.1μm, the operability is good, and if it is below 50μm, it is easy to coat the electrode, so the average particle size of the negative electrode active material is preferably 0.1μm to 50μm, more preferably 0.1μm to 45μm, further preferably 1μm to 10μm, and particularly preferably 5μm.

[0187] In the present disclosure, "particle size" refers to the maximum distance between any two points on the contour line of a particle (the same below). In addition, in the present disclosure, unless otherwise specified, "average particle size" refers to a value calculated as the average value of the particle sizes of particles observed in several to dozens of fields of view using an observation method such as a scanning electron microscope (SEM) and a transmission electron microscope (TEM) (the same below).

[0188] In the above-mentioned slurry, relative to 100 mass % of the negative electrode active material (B), the upper and lower limits of the content of the (A) component are exemplified as 15 mass %, 14 mass %, 13 mass %, 12 mass %, 11 mass %, 10 mass %, 9 mass %, 8 mass %, 7 mass %, 6 mass %, 5 mass %, 4 mass %, 3 mass %, 2 mass %, 1.5 mass %, 1 mass %, 0.5 mass %, etc. In one embodiment, the above-mentioned content is preferably 0.5 mass % to 15 mass %.

[0189] <Conductive additive>

[0190] In one embodiment, the slurry may contain a conductive aid. Examples of the conductive aid include fibrous carbon such as vapor grown carbon fiber (VGCF), carbon nanotube (CNT), carbon nanofiber (CNF); graphite particles; carbon black such as acetylene black, Ketjen black, furnace black; Cu, Ni, Al, Si or their alloys having an average particle size of less than 10 μm, etc. The content of the conductive aid is not particularly limited, and is preferably 0% to 10% by mass, more preferably 0.5% to 6% by mass, relative to the negative electrode active material component.

[0191] <Slurry Viscosity Adjusting Solvent>

[0192] The slurry viscosity adjusting solvent is not particularly limited, and may include a non-aqueous medium having a normal boiling point of 80° C. to 350° C. The slurry viscosity adjusting solvent may be used alone or in combination of two or more. Examples of the slurry viscosity adjusting solvent include amide solvents such as N-methylpyrrolidone, dimethylformamide, and N,N-dimethylacetamide; hydrocarbon solvents such as toluene, xylene, n-dodecane, and tetralin; alcohol solvents such as methanol, ethanol, 2-propanol, isopropanol, 2-ethyl-1-hexanol, 1-nonanol, and lauryl alcohol; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, phorone, acetophenone, and isophorone; ether solvents such as dioxane and tetrahydrofuran (THF); ester solvents such as benzyl acetate, isoamyl butyrate, methyl lactate, ethyl lactate, and butyl lactate; amine solvents such as o-toluidine, m-toluidine, and p-toluidine; lactones such as γ-butyrolactone and δ-butyrolactone; sulfoxide / sulfone solvents such as dimethyl sulfoxide and sulfolane; water, etc. Among them, N-methylpyrrolidone is preferred from the viewpoint of coating workability. The content of the non-aqueous medium is not particularly limited, but is preferably 0% by mass to 10% by mass relative to 100% by mass of the slurry.

[0193] The slurry may contain, as an additive, a substance that is not included in any of the components (A), (B), water, a conductive additive, and a slurry viscosity adjusting solvent, within a range that does not impair the effects of the present invention. Examples of the additive include the above-mentioned additives.

[0194] The content of the additives relative to 100 mass % of the component (A) is exemplified by 0 mass % to 5 mass %, less than 1 mass %, less than 0.1 mass %, less than 0.01 mass %, 0 mass %, and the like.

[0195] The content of the additive relative to 100 mass % of the component (B) is exemplified by 0 mass % to 5 mass %, less than 1 mass %, less than 0.1 mass %, less than 0.01 mass %, 0 mass %, and the like.

[0196] In addition, about dispersion (emulsion), it is also possible to contain in an amount more than the content of the above-mentioned additive. Relative to 100% by mass of slurry for negative electrode of lithium ion battery, the upper and lower limits of the content of dispersion (emulsion) are exemplified as 20% by mass, 19% by mass, 17% by mass, 15% by mass, 13% by mass, 10% by mass, 9% by mass, 7% by mass, 5% by mass, 4% by mass, 2% by mass, 1% by mass, 0% by mass, etc. In one embodiment, from the viewpoint of resilience resistance and discharge capacity retention rate, relative to 100% by mass of the above-mentioned aqueous solution or the above-mentioned slurry for negative electrode of lithium ion battery, the addition amount of dispersion (emulsion) is preferably less than 5% by mass.

[0197] The slurry is produced by mixing the component (A), the component (B), and water, and, if necessary, a conductive additive and a slurry viscosity adjusting solvent.

[0198] Examples of the mixing means for the slurry include a ball mill, a sand mill, a pigment disperser, a pounder, an ultrasonic disperser, a homogenizer, a planetary mixer, and a Hobart mixer.

[0199] [Lithium-ion battery negative electrode]

[0200] The present disclosure provides a negative electrode for a lithium ion battery, which is obtained by applying the above-mentioned negative electrode slurry for a lithium ion battery on a current collector and drying and solidifying it. The above-mentioned negative electrode for a lithium ion battery has a solidified product of the above-mentioned negative electrode slurry for a lithium ion battery on the surface of the current collector.

[0201] The current collector may be any of various known current collectors without particular limitation. The material of the current collector is not particularly limited, and examples thereof include metal materials such as copper, iron, aluminum, nickel, stainless steel, and nickel-plated steel; and carbon materials such as carbon cloth and carbon paper. The shape of the current collector is also not particularly limited, and in the case of metal materials, examples thereof include metal foil, metal cylinder, metal coil, and metal plate; and in the case of carbon materials, examples thereof include carbon plate, carbon film, and carbon cylinder. Among them, in the case of using the electrode active material for the negative electrode, copper foil is preferably used as the current collector because it is currently used in industrial products.

[0202] The coating means is not particularly limited, and examples thereof include conventionally known coating devices such as a comma coater, a gravure coater, a micro gravure coater, a die coater, and a bar coater.

[0203] The drying means is not particularly limited, but the temperature is preferably 60° C. to 200° C., more preferably 100° C. to 195° C. The atmosphere may be dry air or an inert atmosphere.

[0204] The thickness of the negative electrode (cured product) is not particularly limited, but is preferably 5 μm to 300 μm, more preferably 10 μm to 250 μm. Within the above range, a sufficient Li absorption and release function for a high-density current value can be easily obtained.

[0205] [Lithium-ion battery]

[0206] The present disclosure provides a lithium ion battery including the above-mentioned negative electrode for lithium ion battery. In one embodiment, the above-mentioned battery includes an electrolyte solution, a separator, and a positive electrode, etc. These are not particularly limited.

[0207] Examples of the electrolyte solution include a non-aqueous electrolyte solution in which a supporting electrolyte is dissolved in a non-aqueous solvent. The non-aqueous electrolyte solution may contain a film-forming agent.

[0208] The non-aqueous solvent may be any known non-aqueous solvent without particular limitation, and may be used alone or in combination of two or more. Examples of the non-aqueous solvent include chain carbonate solvents such as diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate; cyclic carbonate solvents such as ethylene carbonate, propylene carbonate, and butylene carbonate; chain ether solvents such as 1,2-dimethoxyethane; cyclic ether solvents such as tetrahydrofuran, 2-methyltetrahydrofuran, sulfolane, and 1,3-dioxolane; chain ester solvents such as methyl formate, methyl acetate, and methyl propionate; cyclic ester solvents such as γ-butyrolactone and γ-valerolactone; acetonitrile, etc. Among them, a combination of mixed solvents containing cyclic carbonates and chain carbonates is preferred.

[0209] A lithium salt may be used as the supporting electrolyte. Various known lithium salts may be used as the lithium salt without particular limitation, and may be used alone or in combination of two or more. Examples of the supporting electrolyte include LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. Among them, LiPF6, LiClO4, and CF3SO3Li, which are easily soluble in a solvent and show a high degree of dissociation, are preferred. The higher the degree of dissociation of the supporting electrolyte used, the higher the lithium ion conductivity, and therefore, the lithium ion conductivity can be adjusted by the type of supporting electrolyte.

[0210] The film forming agent can use various known film forming agents without particular limitation, and can be used alone or in combination of two or more. The film forming agent exemplifies carbonate compounds such as vinylene carbonate, vinyl ethylene carbonate, vinyl ethyl carbonate, methyl phenyl carbonate, fluoroethylene carbonate, and difluoroethylene carbonate; cyclosulfide hydrocarbons such as ethylene sulfide and propylene sulfide; sultone compounds such as 1,3-propane sultone and 1,4-butane sultone; anhydrides such as maleic anhydride and succinic anhydride. The content of the film forming agent in the electrolyte solution is not particularly limited, and is preferably in the order of less than 10% by mass, less than 8% by mass, less than 5% by mass, and less than 2% by mass. By making the content less than 10% by mass, the advantage of the film forming agent is that it is easy to achieve the suppression of the initial irreversible capacity, the improvement of low temperature characteristics and rate characteristics, etc.

[0211] The separator is an article between the positive electrode and the negative electrode, and is used to prevent short circuits between the electrodes. Specifically, porous separators such as porous films and nonwoven fabrics can be preferably used, and these separators are impregnated with the above-mentioned non-aqueous electrolyte and used. The material of the separator can use polyolefins such as polyethylene and polypropylene, polyether sulfone, etc., preferably polyolefins.

[0212] The positive electrode may be any known positive electrode without particular limitation. Examples of the positive electrode include a positive electrode obtained by mixing a positive electrode active material, a conductive aid, a positive electrode binder, and an organic solvent to prepare a slurry, coating the prepared slurry on a positive electrode collector, drying, and pressing the slurry.

[0213] Examples of positive electrode active materials include inorganic positive electrode active materials and organic positive electrode active materials. Examples of inorganic positive electrode active materials include transition metal oxides, composite oxides of lithium and transition metals, transition metal sulfides, etc. Examples of the above transition metals include Fe, Co, Ni, Mn, Al, etc. Examples of inorganic compounds used in positive electrode active materials include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFePO4, LiNi 1 / 2 Mn 3 / 2 O4、LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li[Li 0.1 Al 0.1 Mn 1.8 ]O4, LiFeVO4 and other lithium-containing composite metal oxides; TiS2, TiS3, amorphous MoS2 and other transition metal sulfides; Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, V6O 13Transition metal oxides, etc. These compounds may also be compounds with partial element substitution. Examples of organic positive electrode active materials include conductive polymers such as polyacetylene and polyparaphenylene. By allowing the presence of a carbon source during reduction calcination, iron-based oxides with poor conductivity may also be used as electrode active materials covered with carbon materials. In addition, these compounds may also be compounds with partial element substitution. Among them, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFePO4, LiNi 1 / 2 Mn 3 / 2 O4、LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li[Li 0.1 Al 0.1 Mn 1.8 ]O4.

[0214] Examples of conductive additives include fibrous carbon such as vapor grown carbon fiber (VGCF), carbon nanotube (CNT), carbon nanofiber (CNF); graphite particles; carbon black such as acetylene black, Ketjen black, furnace black; and fine powders of Cu, Ni, Al, Si or their alloys with an average particle size of less than 10 μm.

[0215] The positive electrode binder can be used without particular limitation, and various known positive electrode binders can be used alone or in combination of two or more. Examples of the positive electrode binder include fluorine resins (polyvinylidene fluoride, polytetrafluoroethylene, etc.), polyolefins (polyethylene, polypropylene, etc.), polymers with unsaturated bonds (styrene-butadiene rubber, isoprene rubber, butadiene rubber, etc.), acrylic polymers (acrylic copolymers, methacrylic copolymers, etc.), etc.

[0216] Examples of the positive electrode current collector include aluminum foil and stainless steel foil.

[0217] The form of the lithium-ion battery is not particularly limited. Examples of the form of the lithium-ion battery include a cylindrical type in which the electrode sheet and the separator are spirally shaped; a cylindrical type in which the plate electrode and the separator are combined with an inside-out structure; and a button type in which the plate electrode and the separator are stacked. In addition, by placing these batteries in any outer packaging box, they can be used in any shape such as a button type, a cylindrical type, a square type, etc.

[0218] The manufacturing method of the lithium ion battery is not particularly limited, and can be assembled by taking appropriate procedures according to the structure of the battery. The manufacturing method of the lithium ion battery is exemplified by the method described in Japanese Patent Publication No. 2013-089437. The battery can be manufactured by installing a negative electrode on an outer packaging box, setting an electrolyte and a diaphragm thereon, and then installing a positive electrode so that the positive electrode and the negative electrode are opposite to each other, and fixing them with a gasket and a sealing plate.

[0219] Example

[0220] The present invention is described in detail below by way of examples and comparative examples. However, the description in the above preferred embodiments and the following examples are provided only for the purpose of illustration and are not provided for the purpose of limiting the present invention. Therefore, the scope of the present invention is not limited to the embodiments or examples specifically described in this specification, but is limited only by the scope of the claims. In addition, in each example and comparative example, unless otherwise specified, the numerical values ​​of parts, % and the like are based on mass.

[0221] (A) Production of ingredients

[0222] Production Example 1

[0223] In a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, 1240 g of ion exchange water, 350 g (2.46 mol) of a 50% acrylamide aqueous solution, 56.6 g (0.43 mol) of 2-methoxyethyl acrylate, and 0.23 g (0.0014 mol) of sodium methallyl sulfonate were added, and oxygen in the reaction system was removed by nitrogen gas, and then the temperature was raised to 55°C. 2.1 g of 2,2′-azobis-2-amidinopropane dihydrochloride (2,2′-Azobis-2-amidinopropane dihydrochloride) (manufactured by Nihon Ho Chemical Co., Ltd., product name “NC-32”) and 20 g of ion exchange water were added thereto, and the temperature was raised to 80°C for 3 hours to react. Ion exchange water was added to make the solid content concentration 13% to obtain an aqueous binder solution containing water-soluble poly(meth)acrylamide. The B-type viscosity of the solution at 25°C was 10,000 mPa·s.

[0224] In Production Examples 2 to 4, aqueous binder solutions containing water-soluble poly(meth)acrylamide were prepared in the same manner as in Production Example 1 except that the monomer composition was changed as shown in the following table.

[0225] Production Example 5

[0226] 1170 g of ion exchange water, 120 g (0.84 mol) of 50% acrylamide aqueous solution, 12 g (0.12 mol) of N,N-dimethylacrylamide, 62.8 g (0.48 mol) of 2-methoxyethyl acrylate, 87 g (0.96 mol) of 80% acrylic acid, and 0.19 g (0.0012 mol) of sodium methallyl sulfonate were added to a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet pipe. After removing oxygen in the reaction system with nitrogen, the temperature was raised to 55° C. 1.8 g of 2,2′-azobis-2-amidinopropane dihydrochloride (manufactured by Nihon Ho Chemical Co., Ltd., product name “NC-32”) and 20 g of ion exchange water were added thereto, and the temperature was raised to 80° C. to carry out a reaction for 3 hours. Then, 64.4 g (0.77 mol) of a 48% sodium hydroxide aqueous solution was added as a neutralizing agent and stirred, and ion exchange water was added to adjust the solid content concentration to 13% to obtain an aqueous binder solution containing water-soluble poly(meth)acrylamide. The B-type viscosity of the solution at 25°C was 12,000 mPa·s.

[0227] In Production Examples 6 and 7, except that the monomer composition and the amount of the neutralizing agent were changed as shown in the following table, an aqueous binder solution containing water-soluble poly(meth)acrylamide was prepared in the same manner as in Production Example 5.

[0228] Comparative Manufacturing Example 1

[0229] 1280g of ion exchange water, 500g (3.52mol) of 50% acrylamide aqueous solution, and 0.28g (0.0018mol) of sodium methallyl sulfonate were added to a reaction device equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube. After removing oxygen in the reaction system by nitrogen, the temperature was raised to 55°C. 2.3g of 2,2′-azobis-2-amidinopropane dihydrochloride (manufactured by Nihon Kagaku Co., Ltd., product name "NC-32") and 20g of ion exchange water were added thereto, and the temperature was raised to 80°C for 3 hours to react. Then, ion exchange water was added to make the solid content concentration 13%, and an adhesive aqueous solution containing water-soluble poly (meth) acrylamide was obtained. The B-type viscosity of the solution at 25°C was 15,000mPa·s.

[0230] In Comparative Production Examples other than Comparative Production Example 1, aqueous solutions containing water-soluble poly(meth)acrylamide were prepared in the same manner as in Comparative Production Example 1 except that the monomer composition and the like in Comparative Production Example 1 were changed as shown in the following table.

[0231] B-type viscosity

[0232] The viscosity of each binder aqueous solution was measured at 25° C. under the following conditions using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., product name “B-type viscometer BM”).

[0233] Use No.3 rotor at 6 rpm.

[0234] Weight average molecular weight

[0235] The weight average molecular weight was determined as a polyacrylic acid conversion value measured by gel permeation chromatography (GPC) in a 0.2 M phosphate buffer / acetonitrile solution (90 / 10, pH 8.0). The GPC apparatus used was HLC-8220 (manufactured by Tosoh Corporation) and the column used was SB-806M-HQ (manufactured by SHODEX).

[0236]

[0237] AM: Acrylamide (manufactured by Mitsubishi Chemical Co., Ltd., “50% Acrylamide”)

[0238] DMAA: N,N-dimethylacrylamide (manufactured by KJ Chemicolor Co., Ltd., “DMAA”)

[0239] MEA: 2-methoxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., “2-MTA”)

[0240] MMEA: 2-Methoxyethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., “2-Methoxyethyl Methacrylate”)

[0241] ·MEEA: 2-Ethoxyethyl Methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., "2-Ethoxyethyl Methacrylate")

[0242] AA: Acrylic acid (manufactured by Osaka Organic Chemical Industry Co., Ltd., "80% acrylic acid")

[0243] HEA: 2-Hydroxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., “HEA”)

[0244] ·AN: Acrylonitrile (manufactured by Mitsubishi Micron Co., Ltd., "Acrylonitrile")

[0245] BA: Butyl acrylate (manufactured by Toagosei Co., Ltd., “Butyl acrylate”)

[0246] SMAS: Sodium methallyl sulfonate

[0247] ·NaOH: Sodium hydroxide (manufactured by Kanto Chemical Co., Ltd., “48% sodium hydroxide solution”)

[0248] Slurry manufacturing and battery production and evaluation

[0249] Example 1

[0250] <Manufacturing of electrode slurry>

[0251] A slurry was prepared using a commercially available homodisperser (“Homodisperser 2.5” manufactured by PRIMIX Corporation). In a mayonnaise bottle as a container, 5 parts by mass of a lithium ion battery binder aqueous solution containing the water-soluble poly(meth)acrylamide (A) obtained in Preparation Example 1, 20 parts by mass of silicon monoxide particles having a D50 (median particle size) of 5 μm (manufactured by Osaka Chitanium Technology Co., Ltd., "CC powder"), 80 parts by mass of artificial graphite having a D50 (median particle size) of 20 μm (manufactured by Jiangxi Zichen Technology Co., Ltd., "G1-A#"), and 1 part by mass of a conductive aid (manufactured by Imelis Diaman Co., Ltd., "Super C65") were mixed. Ion exchange water was added thereto so that the solid content concentration was 47%, and the container was set in the above-mentioned homogeneous disperser. Then, the mixture was kneaded at 3,000 rpm for 10 minutes and then degassed for 1 minute using a rotary and orbital mixer (manufactured by Shinki Co., Ltd., “Awato Rirentaro”) to obtain an electrode slurry.

[0252] In Examples and Comparative Examples other than Example 1, slurries were prepared in the same manner as in Example 1 except that the composition in Example 1 was changed as shown in the following table.

[0253] <Storage stability test of electrode slurry>

[0254] The storage stability of the electrode slurry was evaluated as follows.

[0255] The electrode slurry was measured for viscosity (unit: mPa·s) with a B-type viscometer and then stored in an oven heated to 40° C. for 3 days. After storage, the viscosity was measured again with a B-type viscometer, and the viscosity change was calculated using the following formula and evaluated according to the following evaluation criteria.

[0256] Viscosity change (%) = {(viscosity of electrode slurry after storage) / (viscosity of electrode slurry before storage)}×100

[0257] A: Less than 110%

[0258] B: 110% or more and less than 120%

[0259] C: 120% or more and less than 130%

[0260] D: 130% or more

[0261] <Evaluation of Electrode Flexibility>

[0262] The flexibility of the electrode is evaluated as follows.

[0263] On the surface of the current collector (20 μm) made of copper foil, the above-mentioned slurry for lithium-ion batteries is uniformly coated by the doctor blade method so that the dried film thickness is 170 μm, and after heating and drying at 150 °C for 15 minutes, it is processed to obtain an electrode. The obtained electrode is cut into a width of 10 mm × a length of 70 mm, and it is wound around a Teflon (registered trademark) rod with the active material layer on the outside, and the surface condition of the active material layer is observed and evaluated according to the following criteria. On a Teflon (registered trademark) rod with a diameter of

[0264] A: No cracking or peeling occurs in the active material layer bonded to the current collector.

[0265] B: Cracking is found in the active material layer bonded to the current collector, but no peeling is found.

[0266] C: Cracking and peeling are found in the active material layer bonded to the current collector.

[0267] <Evaluation of Electrode Adhesion>

[0268] The adhesion of the electrode is evaluated as follows.

[0269] On the surface of the current collector (20 μm) made of copper foil, the above-mentioned slurry for lithium-ion batteries is uniformly coated by the doctor blade method so that the dried film thickness is 170 μm, and after drying at 150 °C for 30 minutes, it is heat-treated at 150 °C / vacuum for 120 minutes. Then, a pressing process is performed using a roll press to make the density of the film (electrode active material layer) 1.5 g / cm 3 , thereby obtaining an electrode. A test piece with a width of 2 cm × a length of 10 cm is cut out from the obtained electrode and fixed with the coated surface facing up. Then, a 15-mm-wide adhesive tape (manufactured by NICHIBAN Co., Ltd., "Cellotape (registered trademark)") (specified in JIS Z1522) is pressed and pasted on the surface of the active material layer of the test piece. After that, at 25 °C, using a tensile testing machine (manufactured by A&D Company, Ltd., "TENSILON RTM-100"), the stress when peeling the adhesive tape from one end of the test piece at a speed of 30 mm / minute in the 180° direction is measured. The measurement is performed twice, and the value is converted to the value per 15-mm width, and the average value is calculated as the peel strength. The greater the peel strength, the higher the adhesion strength between the current collector and the active material layer or the adhesiveness between the active materials, indicating that the active material layer is difficult to peel from the current collector or the active materials are difficult to peel from each other.

[0270] The evaluation of electrode adhesion is shown in the table according to the following criteria.

[0271] AA: 41N / m or more

[0272] A: 30N / m~40N / m

[0273] B: 20N / m~30N / m

[0274] C: less than 20N / m

[0275] <Assembly of lithium half-cell>

[0276] The surface of the collector (20 μm) composed of copper foil was uniformly coated with the above-mentioned slurry for lithium ion batteries by a doctor blade method in a manner that the film thickness after drying was 170 μm, dried at 150°C for 30 minutes, and then heated at 150°C / vacuum for 120 minutes. Then, the film (electrode active material layer) was pressed by a roller press to a density of 1.5 g / cm 3 , thus obtaining an electrode.

[0277] In a glove box replaced with argon, the electrode punched into a material with a diameter of 16 mm was loaded on the inner side of the pad on the Al lower cover of the test cell (manufactured by Japan Tomcell Co., Ltd.). Next, a diaphragm formed of a polypropylene porous film punched into a diameter of 24 mm (manufactured by CS TECH CO., LTD, "Selion P2010") was loaded, and after further injecting 500 μL of electrolyte to prevent air from entering, a commercially available metal lithium foil punched into a material of 16 mm was loaded, and the outer packaging of the test cell was sealed with screws to assemble a lithium half-cell. The electrolyte used here is a solution in which LiPF6 is dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 1 (mass ratio).

[0278] <Charge and discharge measurement>

[0279] The lithium half-cell was placed in a thermostatic chamber at 25°C, and charging was started at a constant current (0.1C), and charging was completed (cut off) when the voltage reached 0.01 V. Next, discharging was started at a constant current (0.1C), and discharging was completed (cut off) when the voltage reached 1.0 V. This charging and discharging cycle was repeated 30 times.

[0280] In addition, under the above measurement conditions, "1C" means the current value at which a battery with a certain capacitance is discharged at a constant current within 1 hour. For example, "0.1C" means the current value at which the discharge is completed after 10 hours, and "10C" means the current value at which the discharge is completed after 0.1 hours.

[0281] <Discharge Capacity Retention Rate>

[0282] The discharge capacity retention rate was calculated by the following formula.

[0283] Discharge capacity retention rate = {(discharge capacity at the 30th cycle) / (discharge capacity at the 1st cycle)}×100 (%)

[0284] The discharge capacity retention rate was evaluated according to the following criteria and is shown in the table.

[0285] AA: above 90%

[0286] A: 80%~89%

[0287] B: 70%~79%

[0288] C: less than 70%

[0289] [Table 3]

[0290]

Claims

1. A binder aqueous solution for lithium ion batteries, comprising a water-soluble poly(meth)acrylamide (A), The water-soluble poly(meth)acrylamide (A) is a polymer of a monomer group, and the monomer group comprises 30 mol% to 95 mol% of a (meth)acrylamide group-containing compound (a), 5 mol% to 40 mol% of an alkoxyalkyl (meth)acrylate (b) represented by the following general formula (1), and 0 mol% to 40 mol% of an unsaturated organic acid (c), relative to 100 mol% of the monomer group, wherein CH2=C(R 1 )-CO-OR 2 -OR 3 (1) In the formula, R 1 is a hydrogen atom or a methyl group, R 2 is an alkylene group having 1 to 4 carbon atoms, R 3 is an alkyl group having 1 to 4 carbon atoms; in addition, R 1 , R 2 and R 3 The total number of carbon atoms of the group is 5 or less; The (meth)acrylamide-containing compound (a) is (meth)acrylamide, or (meth)acrylamide and N,N-dimethyl (meth)acrylamide; The lower limit of the sum of the contents of the (meth)acrylamide group-containing compound (a), the (meth)acrylate alkoxyalkyl ester (b), and the unsaturated organic acid (c) is 86 mol % relative to 100 mol % of the monomer group.

2. A slurry for a negative electrode of a lithium ion battery comprising the binder aqueous solution for a lithium ion battery according to claim 1 and a negative electrode active material.

3. A negative electrode for a lithium ion battery obtained by applying the slurry for a negative electrode for a lithium ion battery according to claim 2 onto a current collector and drying and solidifying the slurry.

4. A lithium ion battery comprising the negative electrode for a lithium ion battery according to claim 3.

Citation Information

Patent Citations

  • A signal distribution device

    JP1984003761B2

  • Binder for lithium ion battery electrode, paste for lithium ion battery negative electrode using the same and manufacturing method of lithium ion battery negative electrode

    JP2013089437A

  • Slurry for electricity storage device negative electrode and electricity storage device negative electrode, slurry for electricity storage device positive electrode and electricity storage device positive electrode, and electricity storage device

    JP2015106488A

  • Binder composition for electricity storage device, slurry for electricity storage device, electricity storage device electrode, separator, and electricity storage device

    JP2015118908A

  • Binder composition for lithium ion secondary battery, slurry composition for lithium ion secondary battery, method for manufacturing electrode for secondary battery, and lithium ion secondary battery

    WO2015098507A1